1993
DOI: 10.1002/jso.2930540112
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis is rarely the initial presentation of cecal cancer in the elderly patient

Abstract: Acute appendicitis is rarely the initial presentation of carcinoma of the cecum in elderly patients. A 20-year retrospective review of all patients 65 years of age or older presenting with proven acute appendicitis at the Montefiore Medical Center confirms this opinion. In only 1.8% of patients was acute appendicitis the initial presentation of an underlying carcinoma of the cecum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Obstruction of the appendiceal orifice by tumour, particularly carcinoma of the caecum, is an occasional cause of appendicitis in middle-aged and elderly patients 4. Bizer has observed that in 1.8% of patients acute appendicitis is the initial presentation of an underlying caecal carcinoma 5. The present case being an elderly woman with a hard mass in the RIF was diagnosed as carcinoma of the caecum since the mass persisted even after the inflammatory appendicular mass resolved with conservative treatment.…”
Section: Discussionmentioning
confidence: 71%
“…Obstruction of the appendiceal orifice by tumour, particularly carcinoma of the caecum, is an occasional cause of appendicitis in middle-aged and elderly patients 4. Bizer has observed that in 1.8% of patients acute appendicitis is the initial presentation of an underlying caecal carcinoma 5. The present case being an elderly woman with a hard mass in the RIF was diagnosed as carcinoma of the caecum since the mass persisted even after the inflammatory appendicular mass resolved with conservative treatment.…”
Section: Discussionmentioning
confidence: 71%
“…9 The percentage of patients presenting with appendicitis that also have colonic carcinomas is ranging from 1 to 8%. 10,11,12 Therefore, an aggressive surgical approach of cecal masses, with intra-operative abscess drainage and resection should be performed in selected cases to avoid the risk of delaying the diagnosis and unrecognising malignant lesion as well as to achieve a safe and adequate treatment. 13 Careful intraoperative assessment, including evaluation of the bowel involved by the inflammation, inspection and palpation of the liver, resection and examination of the specimen is essential to identify malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the most common neoplastic process is carcinoid tumor of the appendix [2,3,8], which may or may not be diagnosed at the time of appendectomy. Even less commonly, acute appendicitis may be the first presentation for a cecal neoplasm [1,10]. During conventional appendectomy through a laparotomy incision, the cecum and the appendix are easily palpated, and an obvious mass can be detected and properly managed at the time of appendectomy.…”
Section: Discussionmentioning
confidence: 99%